Measuring Consumer-Based Brand Authenticity - Napoli, Julie; Dickinson, Sonia; Beverland, M.; Farrelly, F. (Elsevier, 2014)
Postmodern consumers use brands to create an authentic self and to reconnect to place, time, culture and others. Although previous research has identified that consumers draw on a range of cues in order to attribute authenticity to branded objects, no scales exist to measure the construct of brand authenticity. Building on the existing literature, this paper uses quantitative methods to develop a psychometrically robust measure of brand authenticity from a consumer's perspective. Findings demonstrate convergent, discriminant and predictive validity, whereby 14 items represent three interrelated first order factors labeled quality commitment, sincerity and heritage that correspond with a higher order brand authenticity construct. This study extends our understanding of the consumption of authenticity. Moreover, it provides a tool by which firms can evaluate the effectiveness of strategic decisions designed to deliver an authentic brand offering to consumers. Limitations and directions for future research are discussed.